Debata: Po co nam prawa człowieka? - Juchacz, Piotr W. (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The debate Why do we need human rights? took place on April 10th, 2013 at the Faculty of Social Sciences, Adam Mickiewicz University in Poznań. It was a part of the conference Philosophy is changing the world! organized under the auspices of Public Philosophy & Democratic Education journal. The participants of the debate were the youth from middle and high schools in Poznań and Greater Poland and invited experts from the Institute of Philosophy, AMU: Dr. Karolina M. Cern, Dr. Andrzej W. Nowak, Dr. Krzysztof Przybyszewski. Discussion was moderated by Dr. Piotr W. Juchacz. Youth was asking, inter alia, about what human rights are and how freedom is understood within human rights; whether human rights are associated with the European culture or have universal character; whether international documents relating to human rights are fully respected in Poland; and whether attempts at restricting the access to certain content on the Internet is a violation of human rights.